STRUCTURE – ANTIOXIDANT ACTIVITIES RELATIONSHIP ANALYSIS OF ISOEUGENOL, EUGENOL, VANILIN AND THEIR DERIVATIVES - Nur Aini; Bambang Purwono; Iqmal Tahir (Universitas Gadjah Mada, 2007)
Structure Activity Relationship (SAR) technique between the theoretical parameters and antioxidant activities of isoeugenol, eugenol, vanillin and their derivatives as Mannich reaction products, have been analyzed. Antioxidant activities were examined by oxidation reaction of oleic acid at 60 °C with b-carotene methods, whereas theoretical parameters of the activities were determined by calculating Bonding Dissociation Enthalpy (BDE) and net charge of oxygen atom(-OH) using AM1 semi empiric methods. The result from both test showed in the following orders: BHT > Mannich product of isoeugenol > isoeugenol > Mannich product of eugenol > eugenol > Mannich product of vanillin > vanillin. The antioxidant activities increase with small the BDE value and high the net charge. Electron donating groups will increase the antioxidants activity with lowering the BDE value and increasing the net charge, while electron-withdrawing groups will decrease antioxidants activity.